Pengembangan E-Modul Kimia Materi Asam Basa Berbasis Flip PDF Professional untuk Peserta Didik Kelas XI SMA Negeri 1 Menganti - Vanantia Randi Ashari; Achmad Noor Fatirul; Djoko Adi Walujo (LP. Ma'arif Janggan Magetan, 2023)
The purpose of this study is to produce an e-module for class XI students of SMA Negeri 1 Menganti acid base material that is interesting and easier for students to understand by using Flip PDF Professional. This research is a development research. The e-module development in this study uses the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. At the analysis stage, an analysis of the curriculum, student characteristics, teaching materials, and materials was carried out. In the design phase, an e-module development design plan is created. The development stage is e-module development, review, expert validation test (media experts, design, materials, and colleagues), and revision. The implementation stage is the implementation of the e-module trial. There are three module trials, namely small, medium and large groups. At the evaluation stage, questionnaires were given to students' responses. The results of chemical e-module validation by design experts, media experts, material experts and colleagues obtained successive percentages of 90%, 85.33%, 90% and 91%, and were declared very valid. The chemical e-module for acid-base materials received very good responses in small, medium and large group trials with percentages of 93%, 92.6% and 90.03%.